ANTIOXIDANT PROPERTIES OF AQUEOUS MEDIA WITH MOLECULAR HYDROGEN AND THEIR USE IN ECO-FRIENDLY MEDICINE - A. A. Lapin; I. G. Garifullin; S. D. Litvinov; V. N. Zelenkov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
This article demonstrates experimental data from the study evaluating total antioxidant activity of water systems saturated with hydrogen using coulometric analysis applied in the Clinic of Ecological Medicine LLC.